Estimation of carbon in Jatropha curcas L. biomass and carbon footprint in its seed production - Sulaiman, Muhammad Firdaus (2011)
Biofuel from plants is claimed to be carbon neutral where unlike fossil fuel, carbon dioxide (CO2) produced from the combustion of biofuel is the same CO2 assimilated by the plant during photosynthesis. Among the plants that are attracting attention nowadays is Jatropha curcas. However, before biofuel from Jatropha curcas could be labeled as carbon neutral, CO2 emission and/or sequestration from all sources of the production chain must first be quantified. The present study was therefore carried out from July 2009 until July 2010 at the Tanah Merah Estate, Port Dickson, Negeri Sembilan to (i) quantify carbon fixation through dry matter production of Jatropha curcas biomass, (ii) compare the carbon balance between land cultivated with Jatropha curcas and the land in its native state and (iii) establish a carbon footprint of Jatropha curcas seed production. Measurements were made at two different plots, one plot planted with Jatropha curcas while the other plot was the native state of the area. Soil CO2 flux and soil total and labile carbon were measured monthly while monthly plant biomass of Jatropha curcas was estimated from monthly stem diameter measurements 20 trees and an established allometric equation. The estimated biomass was then converted to amount of carbon stored based on analysis of biomass carbon content. In comparing the carbon balance between the two types of land use, carbon balance was calculated as the amount of carbon stored in biomass minus the amount of carbon emitted as soil flux and emissions associated with the use of agricultural inputs. The carbon footprint of Jatropha curcas was calculated by dividing the total emitted carbon by the amount of yield (i.e. seed). Results from this study showed that 2.46 Mg carbon ha-1 was sequestered in biomass of Jatropha curcas while emission from Jatropha curcas cultivation was 9.12 Mg carbon ha-1. Soil carbon at both plots did not show any significant changes (P<0.05) throughout this study. Comparison between the two plots showed that emission from the plot planted with Jatropha curcas was marginally higher than at the natural state plot by only 1.20 Mg carbon ha-1. The minimum carbon footprint value of Jatropha curcas cultivation during the first year of its cultivation was 2.96 Mg carbon Mg seed-1.